2011
DOI: 10.1111/j.1365-2516.2011.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance and causes of abnormal preoperative coagulation test results in children

Abstract: To prevent bleeding related to adenoidectomy and tonsillectomy, coagulation screening tests were, until recently, performed routinely in the Czech Republic for all paediatric patients. The aim of this study was to evaluate benefit of preoperative coagulation screening tests in children. We retrospectively analysed laboratory and clinical data of children referred for abnormal preoperative coagulation test results (aPTT, PT) to the outpatient haematology clinic. A total of 274 paediatric patients were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 10 publications
(7 reference statements)
0
4
0
2
Order By: Relevance
“…Our study is different from other studies as it consisted of cases that were operated on despite the prolonged coagulation test results (7,17,21,22,23). A study reported that PT and/or aPTT were prolonged and surgical intervention was performed only with pro-coagulants and/or antifibrinolytics in mild factor deficiencies, and none required specific treatment due to bleeding complications (24). Since no specific factor deficiency was detected in our study, procoagulant or antifibrinolytic treatments were planned to be given in case of bleeding.…”
Section: Discussionmentioning
confidence: 84%
“…Our study is different from other studies as it consisted of cases that were operated on despite the prolonged coagulation test results (7,17,21,22,23). A study reported that PT and/or aPTT were prolonged and surgical intervention was performed only with pro-coagulants and/or antifibrinolytics in mild factor deficiencies, and none required specific treatment due to bleeding complications (24). Since no specific factor deficiency was detected in our study, procoagulant or antifibrinolytic treatments were planned to be given in case of bleeding.…”
Section: Discussionmentioning
confidence: 84%
“…Almost all of the above-mentioned works [ 9 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] underline some fundamental aspects, these being as follows: The relative low frequency of screening coagulation test abnormalities in the pediatric population investigated prior to surgery. A consistent incidence of LA/APAs among children with prolonged aPTT, and its significative relationship with recent infections (especially frequent upper air tract infections in children candidates for adenotonsillectomy).…”
Section: Suggestions: a (Possible) Way To “Not To Lose The Horizon”mentioning
confidence: 99%
“…Avaliação pré-operatória em anestesia pediátrica que isso, o prolongamento do TTPa falso-positivo é comumente associado a anticorpos antifosfolipídios, comumente presentes em criança com infecções de vias aéreas ou após vacinação. 14,15 O exame de ECG pré-operatório de rotina não é recomendado em crianças saudáveis. Deve ser solicitado associado ao ecocardiograma em casos de sopro cardíaco patológico, suspeita de doença cardíaca congênita, apneia obstrutiva do sono, escoliose intensa, broncodisplasia pulmonar, doença neuromuscular em neonatos e crianças com menos de seis meses de vida, o qual pode detectar anormalidades de condução, como síndrome do QT longo e síndrome de Wolff-Parkinson-White.…”
Section: Anamnese E Exame Físicounclassified